Interchangeable face-to-face treatment-telehealth model using cloud system - Cardoso, Gabriel H.; Medeiros, Israel Philipe Assunção; Costa, André Luiz Bezerra; Júnior, Julimar Nogueira de Queiroz; Souza, Alessandro José de; Filho, Francisco Sales de Lima (Seven Editora, 2023)
to bring assistance to rural areas of the United States. Although relevant, social and technological factors have limited the advancement of this type of service. However, the worsening of the health crisis caused by the coronavirus highlighted the importance of this type of tool and the need to improve them for the new social, economic and regulatory context. This work presents a new interchangeable face-to-face-telehealth treatment model mediated by an integrated system with cloud operation that combines traditional care with synchronous and asynchronous interactions regulated in Brazil. The system was validated in two medical clinics with the help of several health professionals. After two years of operation, 7,542 appointments were made and 3,677 consultations were recorded in electronic medical records, 1,434 asynchronous consultations were also performed, most of which were returns. Preliminary results indicate that the model is potentially viable for the various branches of health, even if the volume of synchronous consultations is still low. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-007